KAED ICT labs utilization performance report: semester 1 Vs. semester 2 of 2015/2016 - Ayob, Mohd Fairullazi (2016)
An assessment was carried out to evaluate the utilization performance of KAED ICT Labs for Teaching and Learning in comparison between Semester 1 and Semester 2 of 2015/2016 session.